Solar Tide‐like Signatures in the Ionospheric Total Electron Content During the 2018 Sudden Stratospheric Warming Event - Han Ma; Maosheng He; Libo Liu; Wenbo Li; Yuyan Yang; Ruilong Zhang; Yiding Chen; Huijun Le; Hui Zhang; Guozhu Li (Space Weather)
Abstract Atmospheric waves play an important role in the vertical coupling of atmosphere and ionosphere. Recent studies revealed that the mesospheric wave activities associated with sudden stratospheric warming events (SSWs) are more complicated than previously thought. This study investigates the activities of the dominant solar tide‐like harmonics in the ionosphere during SSWs. Significant tide‐like harmonics are present in the residuals of total electron content (TEC) detected by five receivers at different latitudes using signals from BeiDou geostationary (BD‐GEO) C3 satellite during the 2018 SSW. The results reveal that after the SSW onset, the third harmonic enhances and the fourth harmonic weakens at all selected receivers. However, the second harmonic exhibits a response varying with latitude. We then compare the ionospheric tide‐like signatures with those in mesospheric winds observed by four meteor radars. A good agreement is found after the SSW onset. The measurements at Mohe (53.5°N, 122.3°E) show that the response of each specific ionospheric tide‐like signature is similar to the tidal result in the mesospheric winds after the onset of three SSW events in 2017–2019. In addition, we suggest that besides the direct or indirect effects from the interactions of various waves in the lower atmosphere, the non‐sinusoidal waveform of the ionospheric diurnal variation may also contribute to solar harmonic signatures in the ionosphere.